Produção, caracterização e aplicação de carvão ativado a partir de lodo de estação de tratamento de água - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The objective of this work was the production, characterization and application of activated carbon or the water treatment plant of the city of Bagé, in order to propose an alternative use of this waste. The methodology consisted in the preparation of the sludge sample through operations such as drying, milling and sieving. After the activated carbon was obtained through the pyrolysis operation, using a stainless steel reactor at a temperature of 550 oC por 30 min. Two different active carbon were produced, one performing only the pyrolysis of the sludge (CA) and another using the sludge after a chemical activation with zinc chloride and calcium hydroxide (CAP). The produced active carbon were characterized by physical, chemical and morphological analyzes. In order to verify the potential of application of the active carbon produced adsorption tests were carried out with the aim of removing the methylene blue (AM) present in liquid phase, dye commonly used in textile industries. The samples of CA and CAP were characterized and had a specific surface area of 101.9 to 100.3 m².g-1 and pore diameter of 3.2 and 10.8 nm, respectively, being classified as mesoporous particles. Through the thermogravimetric analysis (TGA) the sample of CA did not present peaks of mass loss, indicating that the pyrolysis operation was effective in the removal of the volatile compounds. The CAP sample indicated the presence of a mass loss peak at 500 ºC, this being related to the remaining presence of the chemical compounds used for the chemical activation during the production of the active carbon. The analyzes of MEV showed that the surface of the CA was more rough and with more irregularities, whereas the one of CAP was smoother due to the remaining presence of zinc chloride and calcium hydroxide. The results obtained by studying the adsorption of methylene blue using CA and CAP were promising. The active carbon mass determined in the preliminary tests was fixed at 2 g because the percentage of AM removal was close to 100 %. The results showed that the adsorption kinetics of AM using CA and CAP is rapid, with removal of more than 50 % of the dye in 2 min of the process. The Elovich kinetic model was the best fit for the experimental data, indicating the heterogeneity of the surface of the active carbon and the chemical nature of the adsorption. The adsorption equilibrium isotherm was classified as type IV and the best fit to the isotherm data was observed by the Sips model, with maximum adsorption capacities of 6.4 and 18.4 mg.g-1 for CA and CAP, respectively. Thus, the results of this study proved the possibility of using sludge from the water treatment plant as a raw material for the production of activated carbon and in this way add value to this residue produced in large scale.
Keywords: Engenharia; Lodo; Adsorvente; Carvão; Engineering; Sludge; Adsorbent; Carbon; CNPQ::ENGENHARIAS